Pengaruh Pengetahuan Syariah, Independensi Auditor Dan Keterampilan Teknis Dalam Meningkatkan Efektivitas Audit Syariah - Sigit Trianto; Cris Kuntadi (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
The aim of this research is to analyze the influence of sharia knowledge, auditor independence, and technical skills on the effectiveness of sharia audits. Data comes from previous research and library research. The research results show that sharia knowledge, auditor independence, and technical skills have a significant influence on the effectiveness of sharia audits. Sharia knowledge has the strongest influence, followed by examiner independence and technical skills. This research provides important implications for sharia audit practice. First, it is important for Sharia auditors to have sufficient Sharia knowledge to properly understand the Sharia transactions and activities being audited. Second, auditor independence must be maintained so that auditors can provide objective and impartial audit opinions. Third, sharia auditors must have sufficient technical skills to carry out audits effectively.